Pemotongan daging ikan Toman (Channa micropeltes) dalam pembuatan ikan kering - Restu Restu (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2015)
This research aims to study how to cut meat of Toman fish (Channa micropeltes) in the making dried fish, in order to obtain the products favored by consumers, so it can be applied in producing high quality of dried fish. The results showed that by cutting transversely meat of Toman fish thickness of 2 cm produce the best dried fish, with product specifications: moisture content (25.41 %); protein content (40.41 %); Fat content (1.81%); and organoleptic value (7.64). Overall organoleptic test results to intact and clean appearance; distinctive aroma of dried fish; compact and crisp texture; specific savory taste and dried fish product. Key words : Channa micropeltes, Toman fish, cutting, dried fish